The policing web - Brodeur, Jean-Paul. (New York ; Oxford : Oxford University Press, 2010)
In this comprehensive study, Jean-Paul Brodeur examines the diversity of the policing web. The study also includes a consideration of military policing both when compatible with the values of democracy and when in opposition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Police